2018
DOI: 10.1002/hbm.24394
|View full text |Cite
|
Sign up to set email alerts
|

The neurophysiological basis of developmental changes during sequential cognitive flexibility between adolescents and adults

Abstract: Cognitive flexibility is a major facet of executive functions and often refers to sequential task control; that is, it is very likely that one may re‐encounter a task that has previously been abandoned to carry out a different task. In the context of sequential cognitive flexibility, the “backward inhibition (BI) effect” has been studied quite extensively. Here we ask whether there are age‐related differences between adolescents and adults to overcome BI and what system‐neurophysiological mechanisms underlie t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…Considering neurophysiological processes in developmental studies, it is crucial to note the significance of intra-individual variability in behavioural performance and in EEG data known to change across the lifespan ( Bodmer et al, 2017 ; Li et al, 2004 ; Papenberg et al, 2013 ). This was one reason why we analysed RIDE-decomposed data, which showed more reliable results than standard ERP in developmental studies ( Bodmer et al, 2017 ; Giller et al, 2019 ). In addition to controlling for age-related differences in intra-individual variability, RIDE also allowed us to differentiate underlying event file coding sub-processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering neurophysiological processes in developmental studies, it is crucial to note the significance of intra-individual variability in behavioural performance and in EEG data known to change across the lifespan ( Bodmer et al, 2017 ; Li et al, 2004 ; Papenberg et al, 2013 ). This was one reason why we analysed RIDE-decomposed data, which showed more reliable results than standard ERP in developmental studies ( Bodmer et al, 2017 ; Giller et al, 2019 ). In addition to controlling for age-related differences in intra-individual variability, RIDE also allowed us to differentiate underlying event file coding sub-processes.…”
Section: Discussionmentioning
confidence: 99%
“…Such fluctuations during development pose a general challenge when comparing neurophysiological correlates of cognitive performance across age groups. For developmental studies, RIDE has been shown to be a particularly suitable tool to circumvent these comparability problems ( Bodmer et al, 2018 ; Giller et al, 2019 ). The reason is that RIDE decomposes EEG data into different clusters, based on latency variability.…”
Section: Introductionmentioning
confidence: 99%
“…The same is the case for fronto‐striatal and fronto‐parietal connections and cortices (Rubia et al, 2006 ). These play an important role in response inhibition processes (Bari & Robbins, 2013 ) and have been implicated in the coding of alarm/surprise signals (Dippel et al, 2016 ; Geng & Vossel, 2013 ; Giller & Beste, 2019 ; Giller, Zhang, Roessner, & Beste, 2019 ; Wessel et al, 2016 ). Thus, a possible theoretical framework for the finding that the relationship between resting‐state and task‐related theta activity becomes stronger with increasing age might relate to the completion of structural brain maturation processes and the concomitant changes in long‐range network dynamics that are important for coding alarm/surprise signals.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have adopted the modality switching task ( Zhang et al, 2016a , 2017 ; Wolff et al, 2018 ; Giller and Beste, 2019 ; Giller et al, 2019 , 2020 ). In the experiment by Koch et al (2004) , two tasks included numerical judgment tasks (parity and size), and the third task was a simple reaction task, requiring the simultaneous pressing of two reaction keys when the stimulus appears.…”
Section: Experimental Paradigmsmentioning
confidence: 99%
“…Although researchers have adopted the term BI in the past decades, in our opinion, it is inappropriate to call BI when we check the relevant operational definition and measurement methods. For example, some studies have determined that cognitive deficits (i.e., Parkinson’s disease, Fales et al, 2006 ), underdeveloped brains (i.e., adolescents, Giller et al, 2019 ), and aging brain functions (i.e., elderly, Giller and Beste, 2019 ) will lead to greater BI effects. However, some previous researches believe that the BI effect reflects the intensity of inhibition.…”
Section: Introductionmentioning
confidence: 99%